2014
DOI: 10.1186/1471-2458-14-833
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among people living with hypertension in a rural Vietnam community

Abstract: BackgroundTo respond to growing prevalence of hypertension in Vietnam, it is critical to have an in-depth understanding about quality of life (QOL) among people living with hypertension and related factors. This study aimed to measure QOL among hypertensive people in a rural community in Vietnam, and its association with socio-demographic characteristics and factors related to treatment.MethodsThis study was conducted in a rural community located 60 km from Ho Chi Minh City. Face-to-face interviews were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
70
8
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 32 publications
28
70
8
5
Order By: Relevance
“…Regarding gender, women evidenced worse perception of QOL than men in all domains, but only for the psychological domain the difference was statistically significant. The same result was observed by other authors 19,27,35 , and the relationship between female gender and psychosocial factors is well reported in studies in the literature, where women reported having more negative feelings, low self-esteem and depression than men 36,37 . Living without partners was associated with a lower perception of QOL in the social relationship domains, as observed by other authors 12,19,38 .…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Regarding gender, women evidenced worse perception of QOL than men in all domains, but only for the psychological domain the difference was statistically significant. The same result was observed by other authors 19,27,35 , and the relationship between female gender and psychosocial factors is well reported in studies in the literature, where women reported having more negative feelings, low self-esteem and depression than men 36,37 . Living without partners was associated with a lower perception of QOL in the social relationship domains, as observed by other authors 12,19,38 .…”
Section: Discussionsupporting
confidence: 78%
“…The same result was observed by other authors 19,27,35 , and the relationship between female gender and psychosocial factors is well reported in studies in the literature, where women reported having more negative feelings, low self-esteem and depression than men 36,37 . Living without partners was associated with a lower perception of QOL in the social relationship domains, as observed by other authors 12,19,38 . Individuals without partners tend to perform poorly on structural aspects of social support networks, such as less contact with family and friends and low frequency of assistance received and provided 39 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…There is an increasing search for assessment of the quality of life of hypertensive subjects because this is considered an important indicator to identify the health status of individuals in face of the results of antihypertensive treatments. (16) Besides medical treatment, it is essential that hypertensive individuals follow a nonpharmacological treatment, which consists of care for the management of weight control, diet, reduction of salt and alcohol consumption, smoking abstention, stress management and regular practice of physical activity. (17) The findings of this study showed that among the possible managements of nonpharmacological treatments, the regular practice of physical activity was the item of greatest commitment, since more than 50% of participants did not have this habit.…”
Section: Discussionmentioning
confidence: 99%